Pengaruh Kualitas Produk dan Pelayanan Terhadap Kepuasan Pelanggan Di Advan Store Mall Ambasador - Muhammad Faisal Basri; Nurvi Oktiani; Syahrir Syahrir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of product quality and service quality on customer satisfaction at Advan Store Mall Ambasador. The research method used is a quantitative approach with a survey technique to 80 respondents who are Advan customers. Data were collected using a closed questionnaire with a five-point Likert scale and processed using multiple linear regression analysis through the SPSS version 25 program. The results of the study indicate that both product quality and service quality have a positive and significant effect on customer satisfaction partially and simultaneously. The t-test value for the product quality variable is 2.737 (significance 0.008) and for the service variable is 2.450 (significance 0.017), which means both have a significant effect on customer satisfaction. Meanwhile, the F-test result of 10.699 with a significance value of 0.000 <0.05 indicates that together product quality and service have a significant effect on customer satisfaction. The coefficient of determination of 49.76% indicates that almost half of the variation in customer satisfaction can be explained by these two variables, while the rest is influenced by other factors outside the study. Thus, improving product and service quality is an important factor for Advan in building customer satisfaction and loyalty amidst increasingly tight competition in the electronics market.